Conhecimento da enfermagem sobre fitoterapia: ferramenta para promoção de saúde e cuidado - (:unkn) unknown (Universidade Federal do Pampa, 2016)
Phytotherapy has been used for millennia as a method of healing, treatment or prevention of diseases and diseases based on accumulated knowledge and information, being part of the culture of different peoples. This article aimed to analyze the knowledge of nurses of the Family Health Strategies of the municipality of Alegrete on phytotherapy and medicinal plants and how they manage this knowledge in the orientation of SUS users. It is characterized in descriptive exploratory with qualitative approach, the results were submitted to simple statistical operations. The data collection for the research was performed through an interview, with the application of a questionnaire with semi-structured questions, which consisted of open and closed questions. 14 nurses working in 13 Family Health Strategies (ESF) in the city of Alegrete, Rio Grande do Sul, Brazil, were interviewed. Professionals use phytotherapy in their care routine, and it was verified that the knowledge about this theme is almost exclusive to tradition Cultural, all believe in the effectiveness of the use of medicinal plants. Even idealizing the use of the species, these do not consider that the plants can pose any health risk, because they do not have a comprehensive knowledge about the subject, this ignorance comes from graduation and persists in professional practice, requiring training and studies to better Assistance they provide.
Nursing knowledge about phytotherapy: tool for health promotion and care
Keywords: Fitoterapia; Plantas medicinais; Phytotherapy; Medicinal plants; Knowledge; Nurses; Enfermeiros; Enfermagem; Nursing; CNPQ::CIENCIAS DA SAUDE